IDENTIFIKASI KEANEKARAGAMAN SERANGGA PADA TANAMAN LEMON (Citrus limon L.) DI PT. AL-FATIH PORANG INDONESIA - Nilam Cahya Agussalim; Rifni Nikmat Syarifuddin; Reza Asra (ITB AAS Indonesia Surakarta, 2024)
Abstract Lemon plantations (Citruslimon L.) are popular fruit plantations because they have benefits and nutritional content of various vitamins so that demand for lemons in the community increases. One of the factors that influences the growth, development and production of lemons is the presence of various types of insects, both beneficial and detrimental. PT. Al-Fatih Porang Indonesia is a company operating in the agricultural sector that cultivates lemons with a plantation area of 80 Ha. The aim of this research is to find out the types of insects that are in lemon plantations and to identify types of insects that have the potential to become natural enemies of pests in lemon plantations. The research that will be used is descriptive research by describing the types of insects in lemon plantations. Insects were collected using absolute methods (direct observation) and relative methods (20 pitfall traps, 8 yellow traps, 5 attractants with methyl eugenol, sweep net) with collection times, namely every day for three days every week for 6 weeks. Insect collection is carried out at diagonal points in the lemon garden. There are 19 types of insect species found in lemon plantations, namely ants (tapinoma sp.), bedbugs (S. Coarctata), mealybugs (P. Citriculus), orange leaf caterpillars (Papilio sp.), crickets (Gryllus sp.), fruit fly (Bactrocera Dorsalis), beetle (C. Transversalis), house fly (M. Domestica), wasp moth (A. Huebneri), longhorned beetle (P. Punctate), skipper butterfly (C. Tripuctus), cockroach asia (B. Asahinai), volucella zonaria (V. Zonaria), Chlaenius, dragonfly (O. Sabina), bark beetle(D. Maculatus), night beetle(Adoretus), carpenter bee(Xylocopa), woodhopper (V. Nigricornis). There are three types of insect species that have the potential to be natural enemies of lemon plantation pests, namely ants (tapinoma sp.), crickets (Gryllus sp.), zonaria bee flies (V. Zonaria). The output of this research is a research report and scientific article which will be published in accredited journal (synta 4). Keywords: Diversity Of Insects, Lemons, Order